CONTEMPORARY VOICES FROM EGER. A CROSS-SECTION FROM THE PIANO WORKS OF LÁSZLÓ KÁTAI - CSÜLLÖG, Judit; VÁRADY, Krisztina (Studia Universitatis Babes-Bolyai Musica, 2020)
The main purpose of the article is introducing the Hungarian contemporary composer, László Kátai. He is a retired associate professor who worked for almost 30 years at the Music Department of Eszterházy Károly College (Eger, Hungary). His compositions are strongly connected to Hungarian folk music and his musical language is based on Béla Bartók’s style amongst some other influences. The analysis of four piano compositions is the essence of the study.